We Are Not Numbers : the voices of Gaza's youth / Ahmed Alnaouq and Pam Bailey. - Alnaouq, Ahmed; Bailey, Pam (Journalist) (Penguin Books, 2026)
We Are Not Numbers (WANN) was founded to give a voice to the youth of Gaza. Since then, young Palestinians, mostly living in the besieged Gaza Strip, have used the platform to chronicle the human impact of occupation and blockade. In doing so, they have passionately fought to be recognised not as numbers but as human beings with lives, hopes, and dreams. Ten years on, this collection brings together the most impactful essay contributions of the last decade from emerging Palestinian writers, offering a sobering, tender, inspiring, and humanising view of Palestine through the eyes of its next generation of leaders. In an epilogue covering the most recent war in Gaza, the collection's editors Ahmed Alnaouq and Pam Bailey reflect on the personal tragedies they have faced, as well as those writers able to take WANN's work forward and those no longer alive to do so.